Islam and biomedical research ethics - Suleman, Mehrunisha, author.
1 online resource.
Keywords: "This book is a contribution to the nascent discourse on global health and biomedical research ethics involving Muslim populations and Islamic contexts. It presents a rich sociological account about the ways in which debates and questions involving Islam within the biomedical research context are negotiated - a perspective which is currently lacking within the broader bioethics literature. The book tackles some key understudied areas including: role of faith in moral deliberations within biomedical research ethics, the moral anxiety and frustration experienced by researchers when having to negotiate multiple moral sources and how the marginalisation of women, the prejudice and abuse faced by groups such as sex workers and those from the LGBT community are encountered and negotiated in such contexts. The volume provides a valuable resource for researchers and scholars in this area by providing a systematic review of ethical guidelines and a rich case-based account of the ethical issues emerging in biomedical research in contexts where Islam and the religious moral commitments of Muslims are pertinent"--